2015
DOI: 10.1370/afm.1719
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Psychological Treatments for Depressive Disorders in Primary Care: Systematic Review and Meta-Analysis

Abstract: PURPOSE We performed a systematic review of the currently available evidence on whether psychological treatments are effective for treating depressed primary care patients in comparison with usual care or placebo, taking the type of therapy and its delivery mode into account. METHODSRandomized controlled trials comparing a psychological treatment with a usual care or a placebo control in adult, depressed, primary care patients were identified by searches in MEDLINE, Embase, Cochrane Central Register of Contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
114
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(127 citation statements)
references
References 38 publications
(49 reference statements)
3
114
1
9
Order By: Relevance
“…Because trials of pharmacological and psychological interventions differ greatly regarding recruitment strategies, patients, control interventions and outcomes, these trials are analyzed separately and reported in a companion article published in this issue. 17 …”
Section: Methodsmentioning
confidence: 99%
“…Because trials of pharmacological and psychological interventions differ greatly regarding recruitment strategies, patients, control interventions and outcomes, these trials are analyzed separately and reported in a companion article published in this issue. 17 …”
Section: Methodsmentioning
confidence: 99%
“…Several systematic reviews have found little or no difference in the effectiveness of different modalities of brief, time limited therapies—either low or high intensity—compared with longer term interventions such as long term psychoanalytic or psychodynamic approaches 56575859606162. A large meta-analysis of 30 studies covering 5159 participants with a range of depressive conditions from chronic subthreshold depression to MDD in the primary care setting found effect sizes in the small to moderate range for a variety of psychological therapies 62.…”
Section: Interventions In Primary Carementioning
confidence: 99%
“…Cognitive behavioral interventions (CBIs) have demonstrated efficacy in reducing depressive symptoms in the general adult population (Linde et al, 2015) but only one randomized controlled clinical trial (Jesse et al, 2015), has shown the preliminary efficacy of a culturally tailored CBI for reducing APDS in rural low-income and minority women with mild to moderate depressive symptoms. That trial showed similar results for African-American women at high-risk for depression.…”
Section: Introductionmentioning
confidence: 99%